Update Carbon-Nanotube Wiring Gets Real. - Patel-Predd, P. (IEEE spectrum)
Could carbon nanotubes have a shot at replacing the copper wires that connect millions of transistors on today's silicon chips? Chip makers replaced aluminum interconnects with better conducting copper ones about seven years ago, but now copper's days are numbered too. Higher- performance chips with more- tightly packed transistors, expected as soon as 2012, will need interconnects less than 40 nanometers wide, at which point copper's resistance will slow signaling down too much. Late last month, at the Materials Research Society's spring meeting in San Francisco, a team of engineers from Stanford and Toshiba reported that they have used carbon nanotubes to wire logic-circuit components on a conventional silicon CMOS chip. They claim to have shown that nanotubes can shuttle data at speeds of a little faster than 1 gigahertz, close to the range of state-of-the-art microprocessors, which run at speeds of 2 to 3 GHz.